PENGELOLAAN HUBUNGAN ANTAR PRIBADI DARI PASANGAN YANG BERKENALAN MELALUI TINDER - Nastiti Laksmita Adi; Turnomo Rahardjo (Interaksi Online, 2019)
This research based on a phenomenon about many of online dating applications that used by many youths to get a couple, one of them is Tinder. The aim of this research is to understanding the benefits of Tinder application as a communication media to compose interpersonal relationships, also to know the management of interpersonal relationships that tied from Tinder application. This research using the interpretif paradigm with phenomenology approach. This research adopted Social Penetration Theory, Expectancy Violations Theory, and also Affection Exchane Theory. To support these theories, it needs addition of the phases of relationships development and self-disclosure concept. This research found that all of the informants used Tinder application unintentionally. The communication that composed from using Tinder application was running well so all of the informants found their each couple as their wish from the application. For the first face to face communication after the formed communication from Tinder application, it found that the 1st and the 4th informants felt little bit awkward when did face to face with their couples. Meanwhile the 2nd and the 3rd informants were fine with first time face to face communication. When the conflicts happened all of the informants agreed to finish the conflict directly.